Research and innovation priorities for enabling legume scaling for development outcomes in Zambia - Varley, Ciara; Johnston, Angharad; Kinkese, Theresa; Recha, John W.M.; Breen, Caitlin; Alamu, Emmanual; Ndlovu, Noel; Silumesi, Mwala; Mushangure, Remeredzai O; Kalumo, Decolius; Longwe, Kareem; Kaonga, Tione P.; et al. (University of Galway and IITA, 2024)
Legumes are critical to agriculture, food security and economic development in Zambia. The EU-funded LEG4DEV project is conducting research & innovation activities with scaling partners in Zambia to enable them to more effectively scale legumes for development outcomes (productivity, health & nutrition, sustainability, livelihood security). Following an intensive schedule of bilateral meetings with stakeholders and potential scaling partners in Lusaka, the LEG4DEV project organised and ran a “Legumes for Development” multistakeholder research prioritisation workshop on September 30th 2022, in Lusaka, Zambia. The LEG4DEV Multistakeholder workshop was held at Lusaka’s Protea Hotel and was opened by Mr. Shadrack Mwale, Acting Director of Agriculture, representing the Zambian Ministry of Agriculture. He highlighted the importance of legume scaling to national development goals of Zambia in relation to agricultural productivity, health & nutrition, sustainability and livelihoods. The LEG4DEV Multistakeholder Zambia workshop was attended by 39 attendees from government, research organisations, universities, donors, NGOs, farmers organisations and companies. The workshop was organised around the six work packages of the LEG4DEV project where workshop participants worked in five interdisciplinary teams to identify their highest priority research questions (both technical and policy/institutional) that the LEG4DEV project research could focus on in Zambia to better enable legume scaling.